Christians Economic Growth Resulted from Integrating Churches’ Entrepreneurship Education to Their Livelihood Status, a Case of Iringa Municipality - Richard Atufigwege Kasesela (Archives of Current Research International, 2023)
This study investigated the contribution of Entrepreneurship Education (EE) by church services to the economic wellbeing of Christians in Iringa Municipality. This study used a case study design as the framework for data collection and analysis, where Semi-structured questionnaire and Key Informant Interviews were used to collect information from the involved Christians who engaged in entrepreneurial activities and accessed entrepreneurship education in a list of four churches including respondents from ELCT-DIRA (60), Catholic Church (10), Seventh Day Adventist Church (10) and Pentecostal Churches (10), the study selected three respondents. Apart from the Christian entrepreneurs, the study involved four (4) church leaders; one from each church and three (3) respondents where officials from the Business Registration and Licensing Agency (BRELA). Tanzania Revenue Authority (TRA) and Iringa Municipality. The study employed a mixed method research approach whereby both qualitative and quantitative approaches were used. The statistical and thematic analysis was used to analyse quantitative and qualitative information collected from the respondents. From the study findings, it is concluded that Christians’ entrepreneurship projects contribute to their economic growth. It is vividly true that entrepreneurship contributes positively to economic growth, hence it is highly recommended that churches should put emphasis on spiritual growth as well as economic growth and the recommendation is Christian entrepreneurs should think of some ways to integrate their church services with entrepreneurship education, provide a supportive environment, useful network for entrepreneurship and to offer access to resources and opportunities such as financial assistance, training programs, market information, suppliers, customers, and partners.